"IMPROVING FISCAL TRANSPARENCY THROUGH THE APPLICATION OF GOOD GOVERNANCE PRINCIPLES IN REGIONAL GOVERNMENT BUDGET MANAGEMENT" - Awaluddin; Eka Nurmala Sari (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The application of good governance principles in local government budget management is a strategic agenda in public sector governance reform, particularly in developing countries facing demands for fiscal transparency, public accountability, and efficient resource use. However, in Indonesia, implementation still faces structural, institutional, and political obstacles. This study aims to analyze the application of good governance principles in local government budget management and its implications for fiscal transparency, public participation, and fiscal accountability. This study uses a qualitative approach through the Systematic Literature Review (SLR) method based on Qualitative Data Analysis (QDA) . Data are sourced from international and national scientific articles, audit reports, fiscal regulations, and government policy documents. The analysis was conducted thematically to identify patterns, obstacles, and dynamics in the implementation of local fiscal governance. The results show that the implementation of good governance has progressed, particularly in the aspects of fiscal transparency and digitalization. However, public participation remains administrative in nature, and fiscal accountability is dominated by post-audit mechanisms. Digital fiscal governance is identified as a new determinant of efficiency and auditability, despite facing limited institutional capacity. The findings strengthen agency theory and public accountability by extending it to a polycentric accountability model involving the central government, the Regional People's Representative Council (DPRD), external auditors, and the public. This research contributes to the development of fiscal governance theory and provides policy recommendations related to digitalization, deliberative participation, and risk-based oversight. A limitation of the study lies in the lack of fiscal outcome measurement; further research is recommended using a mixed methods or cross-regional comparative approach.